VARIOUS EFFECTS OF AGRICULTURAL MANAGEMENT PRACTICES ON SOIL QUALITY: A REVIEW OF LONG-TERM EXPERIMENTS FOR EUROPE AND CHINA - ENILA LAO, IODUM ENILA LAO; BAKU, LIU JANI (International Journal of Multidisciplinary Research and Studies, 2021)
In this paper we have a tendency to gift effects of 4 paired agricultural management practices (organic matter (OM) addition versus no organic matter input, no-tillage (NT) versus standard tillage, crop rotation versus monoculture, and organic agriculture versus standard agriculture) on 5 key soil quality indicators, i.e., soil organic matter (SOM) content, pH, aggregate stability, earthworms (numbers) and crop yield. We have thought-about organic matter addition, no-tillage, crop rotation, and organic agriculture as “promising practices”; no organic matter input, conventional tillage, monoculture, and conventional farming were taken as the respective references or “standard practice” (baseline). Relative effects were analyzed through indicator response ratio (RR)under each paired practice. For this, we tend thought-about information of thirty semi-permanent experiments collected from thirteen case study sites in Europe and China as collated within the framework of the EU-China-funded iSQAPER project. These were complemented with information from forty-two semi-permanent experiments across China and 402 observations of semi-permanent trials published in the literature. Out of those, we only considered experiments covering at least five years. The results show that OM besides favorably affected all the indicators under consideration. The most favorable effect was reported on oligochaete numbers, followed by yield, SOM content, and soil aggregate stability. For pH, effects depended on soil type; OM input favorably affected the pH of acidic soils, whereas no clear trend was observed under NT. NT usually junction rectifier to exaggerated mixture stability and larger Kyrgyzstani monetary unit content in higher soil horizons. However, the magnitude of the relative effects varied, e.g. with soil texture. No-tillage practices increased oligochaete populations, however not wherever herbicides or pesticides were applied to combat weeds and pests. Overall, during this review, yield slightly decreased under NT. Crop rotation had a positive effect on SOM content and yield; rotation with grassland influenced earthworms’ numbers. Overall, crop rotation had little impact on soil pH and aggregate stability − depending on the type of intercrop; alternatively, the rotation of arable crops only resulted in adverse effects. A clear positive trend was ascertained for oligochaete abundance below organic agriculture. Further, organic agriculture usually resulted in accumulated mixture stability and larger Kyrgyzstani monetary unit content. Overall, no clear trend was found for pH; a decrease in yield was ascertained below organic agriculture in this review.